1982
DOI: 10.1002/1097-0142(19820301)49:5<865::aid-cncr2820490507>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer: Retreatment of local recurrence after definitive irradiation

Abstract: Aggressive radiation therapy for the management of inoperable lung cancer has increased tumor control and survival. However, approximately 20% of patients continue to experience local recurrence as the sole manifestation of treatment failure. Seven hundred thirty-four patients were initially treated by radiation therapy for inoperable lung cancer, for recurrence after resection, or as adjunct postoperative therapy. Twenty-nine patients were referred for retreatment of cancer that recurred within the original t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…[7][8][9] Although the number of patients in the present study was not large in comparison with previous reports, the stages of relapsed non-small-cell lung cancer and the prescribed radiation doses were relatively uniform. [10][11][12][13][14] Several suggestive findings in our study may contribute to the future study of relapsed non-small-cell lung cancer after radiation therapy.…”
Section: Discussionmentioning
confidence: 87%
“…[7][8][9] Although the number of patients in the present study was not large in comparison with previous reports, the stages of relapsed non-small-cell lung cancer and the prescribed radiation doses were relatively uniform. [10][11][12][13][14] Several suggestive findings in our study may contribute to the future study of relapsed non-small-cell lung cancer after radiation therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Eleven studies were identified that specifically reported on clinical results for thoracic reirradiation of locally recurrent NSCLC (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), with publication dates ranging from 1982 to 2009. The majority of these studies are retrospective in nature and are characterized overall by the limited quality and comprehensiveness of the patient, tumor, and treatment data reported and analyzed.…”
Section: General Overviewmentioning
confidence: 99%
“…Few studied provided comprehensive pattern-of-failure documentation. Finally, only four studies attempted to evaluate survival according to potential prognostic factors such as interval between first and second RT, PS, age, size, location, or response (5,7,12,15).…”
Section: Overview Of Study Limitationsmentioning
confidence: 99%
“…Outcome data for reirradiation by traditionally fractionated dosages (180 to 300 cGy) showed overall survival (OS) rates of 26% to 59% at 1 year and 11%to 27% at 2-year follow-up. [7][8][9][10] The same studies had median survival times between 5 and 18 months. These poor outcomes data are further exacerbated by the fact that reirradiation of tissue is associated with greater risk of adverse effects than treatment of radiation-naive lung.…”
mentioning
confidence: 91%